ANALISIS TINGKAT PENDAPATAN NELAYAN DI DESA BANYUSANGKA KECAMATAN TANJUNG BUMI KABUPATEN BANGKALAN - Fajrin Rizki Okvinda; Zainal Arifin; M.Sri Wahyudi (Program Studi Ekonomi Pembangunan, 2019)
This study aims to look at the general description of fishermen and determine the level of income of fishermen in village of Banyusangka, Tanjung Bumi District, Bangkalan Regency. The data used in this study are primary data obtained directly at the Tempat Pelelangan Ikan (TPI) data obtained using purposive sampling as many 44 samples of individual fishermen in the village of Banyusangka. Analysis of the data used is descriptivr quantitative to determine income analysis using the calculation of π = TR – TC, the result of this study indicate the average operational costs of fishermen in Banyusangka village is Rp 177.591, while the average net income of fishermen is Rp 272.409 in one fishing trip. Break Even Point in this study shows that the work of fishermen is considered feasible to be continued.